Understanding heavy mineral enrichment using a three‐dimensional numerical model. Issue 2 (30th September 2017) - Bartzke, Gerhard; Schmeeckle, Mark W.; Huhn, Katrin
Abstract: Layered deposits of relatively light and heavy minerals can be found in many aquatic environments. Quantification of the physical processes which lead to the fine‐scale layering of these deposits is often limited with flumes or in situ field experiments. Therefore, the following research questions were addressed: (i) how can selective grain entrainment be numerically simulated and quantified; (ii) how does a mixed bed turn into a fully layered bed; and (iii) is there any relation between heavy mineral content and bed stability? Herein, a three‐dimensional numerical model was used as an alternative measure to study the fine‐scale process of density segregation during transport. The three‐dimensional model simulates particle transport in water by combining a turbulence‐resolving large eddy simulation with a discrete element model prescribing the motion of individual grains. The granular bed of 0·004 m in height consisted of 200 000 spherical particles (D50 = 500  μ m). Five suites of experiments were designed in which the concentration ratio of heavy (5000 kg m −3 ) to light particles (i.e. 2560 kg m −3 ) was increased from 6%, 15%, 35%, 60% to 80%. All beds were tested for 10 sec at a predefined flow speed of 0·3 m sec −1 . Analysis of the particle behaviour in the interior of the beds showed that the lighter particles segregated from the heavy particles with increasing time. The latter accumulated at the bottom of the domain, forming a layer, whereas the lighter particles were transported over the layer forming sweeps. Particles below the heavy particle layer indicated that the layer was able to armour the particles below. Consequentially, enrichment of heavy minerals in a layer is controlled by the segregation of a heavy mineral fraction from the light counterpart, which enhances current understanding of heavy mineral placer formation.